Since \( JL \) is the perpendicular bisector of \( KM \), we have:
\[ KH = HM \]
Given that \( KH = 6y + 3 \) and \( HM = 2y + 7 \), we can set up the equation:
\[ 6y + 3 = 2y + 7 \]
To solve for \( y \), we first subtract \( 2y \) from both sides:
\[ 6y - 2y + 3 = 7 \]
This simplifies to:
\[ 4y + 3 = 7 \]
Next, we subtract 3 from both sides:
\[ 4y = 4 \]
Dividing both sides by 4 gives us:
\[ y = 1 \]
Now we can substitute \( y = 1 \) back into the expression for \( HM \):
\[ HM = 2y + 7 = 2(1) + 7 = 2 + 7 = 9 \]
Therefore, the length of segment \( HM \) is:
\[ \boxed{9} \]